The microtubule cytoskeleton: An old validated target for novel therapeutic drugs - Lafanechère, Laurence (Frontiers in Pharmacology, 2022)
Compounds targeting microtubules are widely used in cancer therapy with a proven efficacy. However, because they also target non-cancerous cells, their administration leads to numerous adverse effects. With the advancement of knowledge on the structure of tubulin, the regulation of microtubule dynamics and their deregulation in pathological processes, new therapeutic strategies are emerging, both for the treatment of cancer and for other diseases, such as neuronal or even heart diseases and parasite infections. In addition, a better understanding of the mechanism of action of well-known drugs such as colchicine or certain kinase inhibitors contributes to the development of these new therapeutic approaches. Nowadays, chemists and biologists are working jointly to select drugs which target the microtubule cytoskeleton and have improved properties. On the basis of a few examples this review attempts to depict the panorama of these recent advances.